2017
DOI: 10.1111/acv.12329
|View full text |Cite
|
Sign up to set email alerts
|

Can fear conditioning repel California sea lions from fishing activities?

Abstract: 10Marine mammal interactions with fisheries create conflicts that can threaten human safety, 11 economic interests, and marine mammal survival. A deterrent that capitalizes on learning 12 mechanisms, like fear conditioning, may enhance success while simultaneously balancing 13 welfare concerns and reduce noise pollution. During fear conditioning, individuals learn the cues 14 that precede the dangerous stimuli, and respond by avoiding the painful situations. We tested the 15 efficacy of fear conditioning using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Understanding the extent and nature of predation occurring both during capture and after release can provide important inputs into risk assessments for fisheries. Understanding predation rates [e.g., With newly developed predation tags that can detect when a fish has been eaten (Halfyard et al, )], as well as testing net methods to repel habituated predators (e.g., Schakner, Götz, Janik, & Blumstein, ) are fruitful areas of research that would greatly benefit our understanding of predation and post‐release mortality. Probability of recapture following release and the factors influencing recapture similarly remain unknown, and relatively unstudied, for commercial fisheries.…”
Section: Synthesis and Knowledge Gapsmentioning
confidence: 99%
“…Understanding the extent and nature of predation occurring both during capture and after release can provide important inputs into risk assessments for fisheries. Understanding predation rates [e.g., With newly developed predation tags that can detect when a fish has been eaten (Halfyard et al, )], as well as testing net methods to repel habituated predators (e.g., Schakner, Götz, Janik, & Blumstein, ) are fruitful areas of research that would greatly benefit our understanding of predation and post‐release mortality. Probability of recapture following release and the factors influencing recapture similarly remain unknown, and relatively unstudied, for commercial fisheries.…”
Section: Synthesis and Knowledge Gapsmentioning
confidence: 99%
“…In a study that investigated follow-up responses after repeated startle elicitation, the majority of tested grey seals (Halichoerus grypus) sensitised to the stimulus, exhibited flight responses, developed place avoidance and showed signs of temporary fear conditioning (Götz and Janik, 2011). These findings kindled research interest in the startle reflex in the context of practical applications such as target-specific predator deterrence from farmed fish stocks and fisheries (Götz andJanik, 2015, 2016;Schakner et al, 2017). Furthermore, this reflex arc is relevant for understanding the physiological mechanisms underlying aversive responses to anthropogenic ocean noise in marine mammals (Harris et al, 2018), but empirical data is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…In ex-situ trials, they showed that it was possible to train the seals to avoid a formerly nonaversive tone (CS) that predicted the aversive ADD sound (US) (Götz & Janik 2011). Schakner et al (2017) aimed to extend the application of fear conditioning to the field, to teach California sea lions (Zalophus californianus) to avoid two types of attractants: commercial live bait barges (where sea lions haul out and eat the bait) and sport fishing boats (where sea lions eat bait and captured fish off hooks). A rapid-onset, broadspectrum sound was designed to elicit an aversive acoustic startle reflex.…”
Section: Learningmentioning
confidence: 99%